Nutritional screening and prevalence of hospital malnutrition risk. University Hospital of the UANL, Monterrey - Ancer Rodríguez, Patricia R.; Porrata Mauri, Carmen; Hernández Triana, Manuel; Salinas Zamora, Karla; Bernal García, Verónica; Trejo Guzmán, Samantha; González García, Blanca; Herrera López, Mayra; De la Torre Salinas, Anel; Rojas Ramírez, Clemente; Galarza Delgado, Dionicio Ángel (UANL. Facultad de Medicina, 2014)
Introduction: Hospital malnutrition risk has prevalence values of 20%-50%, and it is a major health problem in the health institutions worldwide. Objective: To assess the accomplishment of nutritional screening and the prevalence of hospital malnutrition risk in a University Hospital. Materials and methods: A retrospective analysis was carried out with nutritional screening, using primary data from six clinical areas obtained in the period between July 2012 and December 2013. According to previous results in Mexican health institutions and considering a mean malnutrition risk prevalence of 50%, it was calculated that a sample size of 3200 subjects was required for the assessment of valid risk values. Patients with values ≥3 on the Nutritional Risk Screening (NRS, 2002) were classiied as carriers of nutritional risk. Results: A total of 5611 patients (38% of all patients admitted) were studied. The rate of screening declined from 55% in 2012 to 31% in 2013. During the whole period, 3034 patients were classiied with risk of malnutrition (54% prevalence). Conclusions: The prevalence of hospital malnutrition risk was high. The accomplishment of the nutritional screening was deicient, and declined between 2012 and 2013. The lack of nutritional screening does not meet the vital care requirements of hospitalized patients and prevents the timely treatment of those at malnutrition risk.